ANALISIS PERILAKU STICKY COST PADA BIAYA PRODUKSI DAN NON-PRODUKSI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Suci Riskia Vonna; Rulfah M. Daud (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The aim of this research is to investigate whether there is any indication of sticky cost behavior on the production and non-production costs. The cost stickiness can be indicated by response costs of production and non-production costs to changes in net sales. This study is an empirical study using multiple linear regression analysis. The samples of this study are manufacturing companies listed in Indonesia Stock Exchange during 2011-2014. Samples are taken by simple random sampling method. Total sample of companies used are 57 companies.The research results provide of sticky cost behavior indication on production and non-production costs in Indonesian manufacturing company. With the result of this study, non-production costs are sticky but production costs are not sticky. Keywords— sticky costs, production cost, non-production costs